Pengaruh Latihan Kekuatan Otot Lengan Terhadap Peningkatan Pukulan Servis Atas Bola Volly Siswa Ekstrakurikuler SMPN 9 Palopo - Muhammad Yusril Syam; Saman Saman; Irsan Kahar; Rachmat Hidayat (Universitas Hamzanwadi, 2025)
The overhead serve skills of extracurricular volleyball students at SMP Negeri 9 Palopo are still low. One of the causes is weak arm muscle strength, which plays an important role in producing strong and accurate serves. This study aims to determine the effect of arm muscle strength training on improving overhead serve skills. The study used a quasi-experimental method with a pretest-posttest non-equivalent control group design. A sample of 12 students was selected using purposive sampling. The experimental group was given an arm muscle strength training program for 16 sessions (6 weeks) with a frequency of 3 times per week, including push-ups, sit-ups, planks, squat jumps, and dumbbell exercises. The instrument used was an overhand serve ability test that had been tested for validity and reliability. The data were analyzed using the Independent Sample T-Test and Cohen's d effect size. The results showed an increase in the average overhead serve score in the experimental group of 5.17 points (from 12.17 to 17.33), while the control group only increased by 0.67 points. Hypothesis testing showed a significant difference between the two groups (t-count = 6.458; p < 0.001) with a very large effect size (Cohen's d = 4.084). Arm muscle strength training had a significant effect on improving volleyball overhead serving ability.